(untitled) (Revista Iberoamericana de Bioética, 2026)
Mental illness is a complex delimitation of the human condition. It is associated with cognitive, emotional and behavioral changes. A safe diagnosis and treatment of the disease needs to go beyond scientific paradigms, and also consider the different vulnerabilities of the patient. This research focuses on knowing whether the conception of global bioethics—proposed by Van Rensselaer Potter and reflected in the psychiatric experience of Frantz Fanon—broadens the understanding of people in situations of vulnerability and/or psychological suffering in psychiatric care. It offers bibliographical research, divided into three stages: Potter’s conception of global bioethics; Fanon’s psychiatric experience; and contributions of global bioethics in psychiatric care. It concludes that global bioethics expands the bases of psychiatric care, favoring more adequate diagnoses and treatments. This occurs because it recognizes—as Fanon demonstrated—that individuals may become unwell as a result of the pathological structures of society itself.